Neuroprotective Effects of Cerebrolysin in Moderate Traumatic Brain Injury with Nonoperative Lesions: A 6-Month Prospective Cohort Analysis - Boontoterm, Panu; Sakoolnamarka, Siraruj; Urasyanandana, Karanarak (Asian Journal of Neurosurgery, 2025)
Moderate traumatic brain injury (TBI) with nonoperative intracerebral hemorrhage (ICH) presents a significant challenge in neurorehabilitation, often lacking targeted pharmacological interventions. Cerebrolysin, a neuropeptide compound with proposed neurotrophic and neuroprotective properties, may support recovery in this population. This study aimed to evaluate the clinical efficacy and safety of Cerebrolysin in adults with moderate TBI and nonoperative ICH over a 6-month period.In this prospective, single-blind, controlled cohort study, 340 patients aged 18 to 80 years with moderate TBI and nonoperative ICH were enrolled from two tertiary care centers in Thailand between 2022 and 2024. Participants received either standard care plus Cerebrolysin (30 mL/day intravenously for 10 days; n = 160) or standard care alone (n = 180). The primary outcome was functional improvement assessed by the Coma Recovery Scale-Revised (CRS-R). Secondary outcomes included the Barthel Index (BI), modified Rankin Scale (mRS), and 6-month survival. Safety was evaluated by monitoring seizures, cardiovascular events, and recurrent hemorrhage.The Cerebrolysin group demonstrated significantly greater improvement in CRS-R scores at discharge (20.3 ± 2.7 vs. 16.4 ± 2.1; p = 0.013), higher BI, lower mRS scores, and improved 6-month survival (59.4 vs. 27.8%; p < 0.001). No significant differences in adverse events were observed between groups.Cerebrolysin may enhance functional recovery and survival in moderate TBI with nonoperative ICH without increasing adverse effects. While Cerebrolysin showed promising effects, the nonrandomized and single-blind design limits causal inference. Further randomized controlled trials are warranted.
Keywords: traumatic brain injury; Cerebrolysin; Intracerebral hemorrhage; neuroprotection; Coma Recovery Scale-Revised; Barthel Index; modified Rankin Scale; functional recovery; survival